Towards an aporetic poetics: from interpretation to translation in four passages of Defense of Palamedes by Gorgia (Minerva, 2018)
Defense of Palamedes by Gorgias is a text that brings together complementary and antagonistic voices: voices of the school rhetoric, of drama, philosophy, sophist ideas and politics of the late 5th century BC. in Athens. Another particular feature is the treatment of the hero’s speech, whose rhetoric may represent the communicative tragedy of language or its improvement. This paper presents some peculiarities of the Gorgian text in the light of two fields that study it but not always coincide: translation and critical interpretation. Based on Berman's translation criteria (1991), four passages of different Italian translations will be analyzed: Untersteiner (1949); Mazzara (1999), Mariani (2010) and Giombini (2012).
Keywords: Defense; Palamedes; Gorgias; sophistic ideas; translation